Amlodipine induced Gingival Overgrowth in Patients at a Tertiary Level Hospital of Nepal - Sharma, Arun; Joshi, Rinku; Laxmi Rana, Sweta Rajya; Shrestha, Dhan Bahadur; Joshi, Pramod Raj; Khadka, Sitarama (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Background: Amlodipine is a commonly prescribed anti-hypertensive in clinical practice. Gingival overgrowth is a rare side effect of this drug; with a reported prevalence of 1.7-3.3% in literature. Gingival overgrowth can cause aesthetic and functional problems as well as cause hindrance to maintain proper oral hygiene, thereby deteriorating the periodontal condition of the patient. The prevalence of Amlodipine induced gingival overgrowth is poorly defined in our country. Aim: This study aims to assess Amlodipine induced gingival overgrowth in a tertiary level referral hospital of Nepal Army. Materials and Methods: This study was conducted on hypertensive patients with amlodipine therapy under regular follow up in the Department of Internal Medicine of Shree Birendra Hospital from September to December 2017. The data from record keeping was used for the study. Ethical clearance from Institutional Review committee of Nepal Army Institute of Health Sciences was obtained before conducting the study. Results: Out of 507 patients taking amlodipine, 240 were eligible for study and six (2.5%) were found to have amlodipine induced gingival overgrowth. These patients were on a dose of 5-10 mg over six months to 25 years. The gingival overgrowth was correlated with dose and duration which was statistically significant (p<0.05). Conclusion: Low prevalence of amlodipine induced gingival overgrowth and correlation with dose and duration was seen in this short-term study. However further large-scale follow-up studies may be required to assess the severity of the problem.